I have an expression !A+(A.!B)
and on an expression solver, it gives the !A+(A.!B) = !(A.B)?
.
The solver notified that "Apply the Absorption Law" A.B+!A = B+!A
.
I have made the truth tables for both the expressions and the answer was correct. But the problem is I can not understand how the absorption law has got implemented to my expression !A+(A.!B)
?
Can someone please explain in details how the absorption law has got implemented to my expression?
I am going to assume that + = OR
, . = AND
and ! = NOT
.
The absorption law was applied in the very first step:
!A + A.!B
= !A + !B (if the first monomial does not hold, A is "true"
and thus does not need to be checked again)
= !(A.B) (De Morgan's rule)